Manuscript of Hikayat Hang Tuah (MSS: 1713) PNM: a study of decorative binding and its meaning / Azlini Anuar Tan - Anuar Tan, Azlini (2021)
The book of Hikayat Hang Tuah manuscript is one of the important classic Malay literary works in developing the creative arts in the aesthetics design of the Malay civilization. However, this manuscript still lacking in the codicology study on the binding, decorative elements and relationship in the Malay art tradition also, not yet been discovered by other researcher. In that case, this study aims a comprehensive study on the binding manuscript. The objective of this study is to analyze in codicology examination, decorative elements and identity elements in Malay art tradition. A qualitative research method used to conserve historical exploration which apply in Zakaria Ali’s (1989) Malay Aesthetic Principles. As well as, the technical investigation dealt with camera recorded images, macro lens borg scanning material and interview procedure from the experts. As a result, eighteen codicology items were identified and the core elements were vegetal decoration. Most of the decorations have similarities in Malay art tradition such as woodcarving, metalworks and textiles. The beauty of this manuscript associated with Malay aesthetic which concern in the Islamic principles. Codicology study could be extended in the chemistry laboratory research, digital conservation and engineering bookmaking, in post the content in the school curriculum.